2001
DOI: 10.1109/5.939810
|View full text |Cite
|
Sign up to set email alerts
|

Neuroelectronic interfacing with cultured multielectrode arrays toward a cultured probe

Abstract: Efficient and selective electrical stimulation and recording of neural activity in peripheral, spinal, or central pathways requires multielectrode arrays at micrometer scale. At present, wire arrays in brain, flexible linear arrays in the cochlea and cuff arrays around nerve trunks are in experimental and/or clinical use. Twoand three-dimensional brush-like arrays and sieve arrays, with around 100 electrode sites, have been proposed, fabricated in microtechnology, and/or tested in a number of labs. As there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 96 publications
(81 reference statements)
0
20
0
Order By: Relevance
“…To better define the cell-to-electrode distance, electrodes have been coated with ECM proteins, 177 poly lysine, 178,179 or silane-based monolayers. 180 In addition, electroplating of Pt-back 181 or coating metal electrode with electrically conductive polymers (e.g., polypyrrole) 182 can be used to lower the impedance of the electrode sites. Cell positioning onto electrodes can be improved by surface micropatterning to improve the sensitivity and repeatability of MEA recordings.…”
Section: Extracellular Electrode Arrays For Multisite Recording and Smentioning
confidence: 99%
“…To better define the cell-to-electrode distance, electrodes have been coated with ECM proteins, 177 poly lysine, 178,179 or silane-based monolayers. 180 In addition, electroplating of Pt-back 181 or coating metal electrode with electrically conductive polymers (e.g., polypyrrole) 182 can be used to lower the impedance of the electrode sites. Cell positioning onto electrodes can be improved by surface micropatterning to improve the sensitivity and repeatability of MEA recordings.…”
Section: Extracellular Electrode Arrays For Multisite Recording and Smentioning
confidence: 99%
“…The range of resistances is larger in the latter case, indicating that the relative positions of the electrode and cell body play an important role in determining R seal regardless of whether the electrode is completely covered. High quality cell-electrode contacts, where quality is determined by electrode coverage and sealing, will permit selective and reliable recording [33]. Experiments have similarly demonstrated that the sealing resistance increases when the electrode is completely covered by the cell and drops off sharply when any portion is exposed directly to the medium [31].…”
Section: Cell-surface Interactionsmentioning
confidence: 99%
“…Because of the massive amounts of information exchanged between end organs and the brain during seemingly common tasks, future rehabilitative applications, like graded neuromuscular control or for prosthetic vision, will depend on the availability of large-scale, selective neural interfaces [33]. This requires that the neural interface record efferent nervous signaling with enough specificity to reproduce fine motor control [12].…”
Section: Performance Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The neural activities induced by a stimulus, such as an odor, an image or a sound, are routinely recorded by multi-electrode arrays (MEA, see Victor, 1994;Gross, 1995;Rutten et al, 2001;. Usually hundreds or even thousands of local field potentials and neuronal activities are simultaneously recorded at a sample frequency between 1000 Hz and 2000 Hz (Mehring et al, 2003;Todd, 2005).…”
Section: Introductionmentioning
confidence: 99%